In vitro reconstitution of intermediate filaments form mammalian neurofilament triplet polypeptides. - Zackroff, R V (1982)
Intermediate filaments (IF) were reconstituted in vitro from bovine neurofilament triplet polypeptides. Neural IF, solubilized in either low salt or 8 M urea solution, assembled into IF when returned to near-physiological solution conditions. The 68,000-dalton component of the triplet, purified to homogeneity by preparative NaDodSO4 electrophoresis, was renatured and reassembled into short (approximatley 0.05-micrometer) approximatley 10 nm-diameter filaments. These results demonstrate that the triplet polypeptides are components of neural IF and that the 68,000-dalton polypeptide is an IF structural protein.